Pendayagunaan Orang Percaya Menurut Pola Teladan Musa Dan Yesus: Role Model Pertumbuhan Gereja Kemah Injil Indonesia Jemaat Elroi Sorong - Reynhard Ohoitimur; Andris Kiamani (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2024)
Church growth is one of the indicators of church health. Finding a church that is not growing indicates that there is something unhealthy in the church. This was found at the Kemah Injil Indonesia Jemaat Elroi Sorong Church. Based on initial observations, one of the obstacles to church growth is the leadership of the pastor who does not involve and utilize church members in service. This research was conducted to answer the question of how the utilization of believers according to the pattern of Moses and Jesus Role model. The method used is literature study research to support the researcher's analysis. This study found that Moses and Jesus are leaders who can be role models in utilizing believers with indicators, searching/selecting, training/teaching, placing/sending.